The Role of Entrepreneurship and Business Consulting in Companies in Creative Industries - Magdalena Ratalewska, PhD (Problemy Zarządzania, 2018)
The efficiency of operations of a small and medium-sized business depends largely on the entrepreneurial spirit, skills and knowledge, as well as creativity and openness to the introduction of new solutions on the part of its owner. Undoubtedly, with growing awareness of the role of entrepreneurship in management of micro, small and medium-sized companies, demand for various types of advisory services also increases. The aim of the paper is to analyse micro, small and medium-sized companies in the creative industries sector in terms of entrepreneurial behaviour and experience associated with using consulting services. The paper describes the results of the study conducted by means of the CATI (Computer Assisted Telephone Interview) method in 60 companies in the Lodz Region using consulting services and operating in the area of: (i) marketing and advertising, and (ii) computer games and IT. It was a pilot study.